"When people who use drugs can't differentiate between medical care and cops, it's a problem." Compounding risks of law Enforcement Harassment & Punitive Healthcare Policies - Bayla Ostrach; Vanessa Hixon; Ainsley Bryce (BMC, 2024)
Abstract Background Community-based harm reduction programming is widely recognized as an effective strategy for reducing the increased risks for and spread of HIV, HCV, and for reducing the growing rate of overdose deaths among people who use drugs (PWUD). PWUD in the United States (US) are a highly justice-involved population, also at increased risk for law enforcement interaction, arrest, and incarceration. These risks compound and interact in the context of criminalization and law enforcement surveillance. Justice involvement increases risks for overdose and for riskier injecting behavior among PWUD, in turn increasing HCV and HIV risks. In Central and Southern Appalachia specifically, PWUD have identified fear of law enforcement harassment and arrest as a barrier to engaging in harm reduction behavior, and a deterrent to seeking help at the scene of an overdose. Moreover, stigmatizing and punitive treatment in healthcare settings can deter PWUD from seeking care, with life or death consequences. This evaluation research study assessing the successes and impacts of a grant-funded project to increase access to safer drug consumption supplies and overdose prevention education for PWUD, including justice-involved participants of a syringe access program (SAP), in public housing and beyond in a South-Central Appalachian setting used key informant and opportunistic sampling. Mixed-methods data were compiled and collected including secondary program data; primary interview and participant-observation data. Results The evaluation research identified that grant deliverables were largely achieved, despite challenges presented by the COVID-19 pandemic. In addition, SAP participants and staff reported larger themes surrounding grant-funded activities, in which they perceived that widespread local law enforcement harassment of PWUD increased participants' risks for overdose death and infectious disease risks and that punitive local healthcare settings and policies acted as deterrents to care-seeking for many PWUD. Conclusions Overall, the evaluation research found that participants' experiences with and perceptions of local law enforcement harassment combined with their understandings and experiences of local punitive healthcare settings and policies; together compounding and increasing overdose risks and negative health consequences for local justice-involved PWUD.